Intellectual capital and financial performance of commercial banks in Malaysia / Emerline Carol Henry - Henry, Emerline Carol (2011)
This thesis evaluates the intellectual capital efficiency of commercial banks in Malaysia and aims to investigate whether the intellectual capital components have an impact on the financial performance of the commercial banks as well as to identify the intellectual capital components that drive the financial indicators of the commercial banks. The VAIC method used in the measurement of IC by Pulic (2001) is adopted and consists of the sum of human capital, structural capital and capital employed efficiencies. Nonetheless, this study has incorporated an additional component which is ICT efficiency as an important component for evaluating the intellectual capital efficiency of banks. This study is significant to the implementation of Financial Sector Master Plan (FSMP) by the banking institutions to enhance the level of operating efficiency and allow greater strategic focus on business operation in enhancing competition and innovation. This study will help the bankers to see how strong they are in intellectual capital efficiency compared to the foreign banks. The adoption of ICT in commercial banks has brought about many changes in the banking industry which had enhanced competitive pressures in the banking industry. Foreign banks in Malaysia are more innovative and move forward faster than domestic banks because they are able to leverage on the research and development initiative, expertise and off-the-shelf products, or introduce new systems that already have been tested by parent banks. As a result, foreign banks were more capable of identifying and reacting to changes in the market much faster than most domestic banking institutions. They were also able to open new distribution channels that operate beyond the traditional delivery methods for financial services. Therefore this study adds ICT in VAIC in order to study how efficient are the banks in terms of ICT efficiency. Data on calculating the VAIC are taken from 2001 until 2008 of 22 banks which collecting in their annual reports. The results of 22 observations showed that banks have relatively higher ICT efficiency than human capital, structural capital and capital employed efficiencies.